Pest management tactics for the western cabbage flea beetle (Phyllotreta pusilla Horn) on brassica crops - Al-Doghairi, Mohammed A., author; Cranshaw, Whitney, advisor; Bjostad, L. B., committee member; Kondratieff, Boris C., committee member; Stushnoff, Cecil, committee member (Colorado State University. Libraries, 2000)
The western cabbage flea beetle, Phyllotreta pusilla Horn (Chrysomeiidae: Coleoptera), is often the most important insect pest of brassica crops in the Rocky Mountain region. Flea beetle feeding results in chewed pits on the leaves and cotyledons that, when severe, can cause seedling mortality. Less severe feeding can cause delayed plant development and reduce height, yield, and produce quality. Insecticides have long been the most widely utilized control method for flea beetles. In this study, alternative management tactics such as cultural (planting density, interplanting and host plant resistance), mechanical (trapping), and chemical (repellents and insecticides) controls were investigated. In these studies action thresholds were also developed. The western cabbage flea beetle showed feeding preferences within the Brassicaceae. Chinese cabbage, the cabbage cultivars 'Golden Acre' and 'Copenhagen Market' and the broccoli cultivar 'Green Goliath', were significantly most preferred. Cauliflower, Brussels sprout, collard, kale and the cabbage cultivars 'Red Acre'. 'Earliana' and 'Salad Delight' and broccoli cultivars 'Love Me Tender Hybrid' and 'Premium Crop' were significantly least preferred by flea beetles. Within an area, increasing plant density resulted in a significant decrease in flea beetle population infesting individual broccoli plants, but an increase in total number of flea beetles. A 40-cm in-row spacing plant density resulted in a significant decrease in flea beetle numbers in given area, but an increase in numbers infesting individual plants within that area. Interplanting of a more preferred host plant (radish) among a brassica crop can be an effective mechanism to reduce western cabbage flea beetle infestation and subsequent damage. Flea beetle density was highest in plots with no radishes interplanted between broccoli plants. Interplanting radish within broccoli plants did not significantly affect head weight and subsequent yield compared with a sole crop of broccoli. Flea beetles responded significantly to several visual and chemical stimuli. The colors Saturn green, Saturn yellow and white were significantly the most attractive to flea beetles compared to the transparent control. Allyl isothiocyanate baited traps were significantly attractive to western cabbage flea beetle adults. Traps baited with canola oil were significantly less attractive compared to allyl isothiocyanate. Increase in allyl isothiocyanate concentration up to 2% significantly increased the attractiveness of the traps. Some of the insecticides and repellents tested in the field showed efficacy in controlling the adults of western cabbage flea beetle. Thiodan (endosulfan) and Asana (esfenvalerate) were significantly the most effective insecticides. The adult stage of western cabbage flea beetle may be best controlled by the application of Asana for rapid action or by Thiodan for prolonged effect up to two weeks. Margosan-O, SunSpray, Azatin, and diatomaceous earth were significantly the most effective tested repellents. Such repellents may be effective alternatives to conventional synthetic insecticides for the control of western cabbage flea beetle. Western cabbage flea beetle feeding damage affected cabbage and broccoli plants, causing differences in size and weight of growing heads. Head diameter was significantly larger in plots maintained at 0-beetles per plant threshold compared to head diameter from plots maintained at 10-beetles per plant threshold and the control. Yield obtained from plots maintained at 0, 2 and 5-beetles per plant thresholds in 1997 and 0-beetles per plant threshold in 1998 was significantly higher compared to the 10-beetles per plant threshold and the control. Greatest head size reduction and yield loss occurred at the 10-beetles per plant threshold, suggesting an action threshold below that of 10-beetles per plant. The five flea beetles per plant threshold appears to be an appropriate action threshold for flea beetle control on seedling brassica crops.
Keywords: entomology; agronomy